Vertebral osteomyelitis and epidural abscesses caused by Prevotella oralis: a case report - Hemant Goyal; Shitij Arora; Sneha Mishra; Syed Jamil; Uday Shah (Brazilian Journal of Infectious Diseases, 2012)
An interesting case of pyogenic vertebral osteomyelitis with multiple epidural abscesses caused by non-pigmented Prevotella oralis is reported. The patient was a 68-year-old female who presented to the emergency room (ER) with severe pain and tenderness in her lower back with fever. She had recently undergone esophagogastroduodensoscopy (EGD) for complaints of esophageal reflux, which showed submucosal cyst in the esophagus. Magnetic resonance imaging (MRI) of the thoracic spine revealed multiple spinal epidural abscesses with signal enhancement at the level of T6 and T7, suggestive of vertebral osteomyelitis. Two blood cultures drawn one hour apart grew Prevotella oralis. The body fluid aspirated from the abscesses was also positive for the anaerobic commensal P. oralis. Necrosis associated with the submucosal cyst was implicated as the cause of sepsis and osteomyelitis due to this organism.